SOSIALISASI PENTINGNYA VITAMIN A UNTUK OPTIMALISASI PERTUMBUHAN BALITA - Muhatta Muhatta; Fajar Fajar; Romli Gafur; Iwan Setiawan; Syamsul Ma’rip; Tb. Fiki Fahlaifi Musaffa; Rahmat Hidayat; Iwan Gunawan; Angga Sofyan Lutfi; Eva Muti’ah; Basrowi Basrowi (Gapenas Publisher, 2023)
Health is the main thing that needs to be considered in the child's growth and development process. At the age of infants and toddlers, many supplements or vitamins need to be given so that children's growth and development can work optimally. One of them is the provision of vitamin A capsules. Vitamin A is one of the important nutrients for infants and toddlers because vitamin A will protect infants and toddlers from several risks of disease, especially impaired eye function. But this seems to be still common for rural communities, they even still have not gained knowledge about the importance of Vitamin A, for that it is necessary to do socialization. This community service aims to analyze the effect of socialization activities on the importance of Vitamin A on optimizing growth, development of infants and toddlers. the method used in this PKM is the extension method. Data collection techniques through pre-test and post-test. The results of this Community Service show that there is a significant change in the community regarding knowledge about the importance of vit A, as evidenced by the number of people who want to come to socialization events with village posyandu